The Effectiveness of the Pictorial Book to Improve the Understanding of Deaf Students About Nature and Environment in Elementary School - mohammad efendi (Department of Special Education, 2017)
Delay in language development and communication of deaf children is a major problem for themselves and other people. Therefore, management of the education and habilitation needs to be prepared early with hoping that can increase language and communication skills through systematic learning and utilization of appropriate learning material (textbook). The purpose of this study is to describe the feasibility prototype of learning material to improve understanding about nature and the environment for deaf children in the elementary school. The results of the data analysis of this study concluded that the prototype of the pictorial book has contributed significantly to improving deaf children’s understanding of nature and its surroundings, particularly, through the ability to listen and understand meaning of language, ability to read and understand the meaning of language, the ability to write and understand the meaning of language, as well as a functional knowledge of the language.